Factors influencing online patient-reported ratings among shoulder surgeons - Krishna N. Chopra, MA; Sameer R. Khawaja, BS; Anna L. Gorsky, BS; Nicole L. Greene, BA; Frank L. Vazquez, BS; Joanne Y. Zhou, MD; Zaamin B. Hussain, MD, MEd; Michael B. Gottschalk, MD; Eric R. Wagner, MD, MS (JSES International)
Background: Patient-reported ratings serve as a model of satisfaction and can play a major role in patient recruitment. Many variables can influence ratings on physician review websites (PRWs), such as social media use, academic productivity, fellowship type, and practice setting. This study examines such factors and their relationship with average ratings and overall patient engagement on PRWs. Methods: The American Shoulder and Elbow Surgeons directory was queried for all active members who completed either a shoulder and elbow or sports medicine fellowship in the United States. Each name was searched online for professional accounts, and the number of followers was recorded for each. A summated social media presence score was calculated to identify the top 15% of social media users in each cohort. The presence of a practice group or personal website was also recorded, as was a surgeon's practice setting (academic vs. private) and region of practice. H-index was searched on Scopus. Average ratings, number of reviews, and number of comments were collected from Healthgrades, Google Reviews, and Vitals. Results: A total of 231 shoulder surgeons were included in this review. Compared to shoulder surgeons in academic practice, those in private practice had higher mean ratings and patient engagement on PRWs. When comparing fellowships, shoulder and elbow fellowship–trained surgeons had a greater mean number of ratings on Google than those who completed a sports medicine fellowship. The top 15% of social media users had higher average patient ratings and engagement on Healthgrades compared to the rest of the cohort. There was a positive association between h-index and average rating on Google. No significant associations were found between patient satisfaction and the prestige of medical school or residency program. Discussion: Several variables can influence patient satisfaction by way of average ratings and engagement on PRWs. Prospective patients are much more likely to select surgeons with higher ratings; thus, shoulder surgeons can use this information to capitalize on opportunities to improve patient retention, recruitment, and overall patient satisfaction.